Chemometric modeling of organic contaminant sources in surface waters of a mediterranean river basin - Garcia Reiriz, Alejandro Gabriel (2014)
Chemometric methods are applied to the analysis and interpretation of large multivariate data sets obtained in environmental monitoring studies. Concentrations of multiple organic compounds were measured in river samples taken from several sampling sites, at various geographical locations, during a number of campaigns and/or sampling time periods. Samples were collected and analyzed as part of an extensive multi-annual monitoring program from a mediterranean river basin (in Catalonia, at the northeast of Spain) by the Water Quality Regional Agency. Due to the great amount of multivariate data stored in environmental databases and to their complexity, chemometric modeling methods like Principal Components Analysis (PCA) and Multivariate Curve Resolution with Alternating Least-Squares (MCR-ALS) coupled to appropriate mapping representations are proposed for the evaluation of the environmental quality of the studied rivers. Results achieved in this study are intended to be a contribution to water quality assessment and evaluation of contamination of surface waters in river basin, and to support public policies of environmental control and management of the regions under study.